The Effect of Uphill Training on 60-Meter Sprint Speed in Male Students of SMK Negeri 2 Sigi - Christofel Paili; Andi Saparia; Delvi Kristanti Liloi; Christian Kungku (The Future of Education Journal, 2026)
Physical education plays a crucial role in developing students' physical abilities and sports skills, one of which is through the athletics event of short-distance running. The sprint performance in the 60-meter run of male students at SMK Negeri 2 Sigi is still relatively low, necessitating an effective training method. This study aims to determine the effect of uphill running training on the 60-meter sprint speed of male students at SMK Negeri 2 Sigi. The research method used is an experiment with a one-group pretest-posttest design. The sample consisted of 10 male students selected using purposive sampling technique. The research instrument was a 60-meter sprint test conducted before and after the treatment. Data analysis was performed using the Kolmogorov-Smirnov normality test and t-test. The results showed an improvement in the average running time from 9.421 seconds to 9.279 seconds, with a t-value of 5.973 and a significance level of 0.001 < 0.05. Therefore, it can be concluded that uphill running training significantly affects the improvement of 60-meter sprint speed in male students at SMK Negeri 2 Sigi.